k = 1 ∑ 2 0 ( α 3 k + β 3 k + ξ 3 k )
⎩ ⎪ ⎨ ⎪ ⎧ f ( − 1 ) = − 9 f ( 1 ) = − 7 f ( 3 ) = 1 9
If f ( x ) is monic cubic polynomial having roots α , β , ξ . Then evaluate topmost expression modulo 17.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = x 3 + b x 2 + c x + d
∴ ⎩ ⎪ ⎨ ⎪ ⎧ b + c + d = − 8 b − c + d = − 8 2 7 + 8 b + 3 c + d = 1 9
⇒ b = c = 0 , d = − 8
⇒ f ( x ) = x 3 − 8
Now roots of f ( x ) are 2 , 2 ω , 2 ω 2 where ω is cube root of unity.
∴ ∑ k = 1 2 0 ( α 3 k + β 3 k + ξ 3 k ) = ∑ k = 1 2 0 ( 2 3 k + ( 2 ω ) 3 k + ( 2 ω 2 ) 3 k )
= ∑ k = 1 2 0 2 3 k ( 1 + ω 3 k + ω 6 k ) = ∑ k = 1 2 0 2 3 k ( 3 ) ∵ ω 3 = 1
∑ k = 1 2 0 2 3 k ( 3 ) mod 1 7 = 1 5
How did you get your last statement?
I mean, How can you directly say, ∑ k = 1 2 0 2 3 k ( 3 ) = 1 5 ( m o d 1 7 ) ?
Log in to reply
Here's a nice shortcut I used: k = 1 ∑ 1 6 8 k = 1 − 8 1 − 8 1 7 − 1 Use that 8 1 7 ≡ 8 ( m o d 1 7 ) (Fermat's little theorem) so the fraction becomes 1 and the sum is 0 mod 17. Therefore, what you really need to find is: k = 1 ∑ 4 8 k ≡ 5 ( m o d 1 7 ) I did this last sum by hand, which isn't all that time consuming since it's only 4 terms. Then just multiply by 3 to get the answer.
Log in to reply
I messed up at the last step. Forgot to multiply by 3. Dumbest mistake in the history of brilliant perhaps.
Last statement is computational work and can be solved .Crux of problem was to get it to last step.And observe it is gp.
I got till as far as the roots of the Polynomial. How to proceed Further?
Please elaborate a bit on your solution :)
Log in to reply
Actually I took 2^3k common out of whole expression.
Skills dsv sdvdfbfgnhnghmb hmghm m ghghvgc cgnfgc nfgn fdb fdnfvg ndf nf nfgb mfbh fcgm b
Problem Loading...
Note Loading...
Set Loading...
Finding f ( x ) :
If f ( x ) = ( x + 1 ) ( x − 1 ) ( x − 3 ) + a ( x − 1 ) ( x − 3 ) + b ( x − 3 ) + c , then: ⎩ ⎪ ⎨ ⎪ ⎧ 8 a − 4 b − 2 b + c + c c = − 9 = − 7 = 1 9 ⟺ ⎩ ⎪ ⎨ ⎪ ⎧ a = 3 b = 1 3 c = 1 9 ⟹ f ( x ) = ( ( x + 1 + a ) ( x − 1 ) + b ) ( x − 3 ) + c = x 3 − 8
Finding the value of the expression:
Clearly, α 3 = β 3 = ξ 3 = 8 and α 3 k + β 3 k + ξ 3 k = 8 k + 8 k + 8 k = 3 ⋅ 8 k .
The topmost expression is ∑ k = 1 2 0 3 ⋅ 8 k = 3 ⋅ ∑ k = 1 2 0 8 k = 3 ⋅ 8 ⋅ 8 − 1 8 2 0 − 1 = 7 2 4 ( 8 2 0 − 1 ) = 7 2 4 ( 2 6 0 − 1 ) .
Modulo 17, as 2 4 = 1 6 ≡ − 1 : the answer is 7 2 4 ( 2 6 0 − 1 ) ≡ 7 7 ( ( 2 4 ) 1 5 − 1 ) ≡ ( − 1 ) 1 5 − 1 = − 2 ≡ 1 5 .